2022
DOI: 10.3390/ijms23031683
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials as Ultrasound Theragnostic Tools for Heart Disease Treatment/Diagnosis

Abstract: A variety of different nanomaterials (NMs) such as microbubbles (MBs), nanobubbles (NBs), nanodroplets (NDs), and silica hollow meso-structures have been tested as ultrasound contrast agents for the detection of heart diseases. The inner part of these NMs is made gaseous to yield an ultrasound contrast, which arises from the difference in acoustic impedance between the interior and exterior of such a structure. Furthermore, to specifically achieve a contrast in the diseased heart region (DHR), NMs can be desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 128 publications
0
7
0
Order By: Relevance
“…SiO 2 NPs are common inorganic materials with natural echogenic properties, and they have recently been proposed as UCAs for CEUS due to the differences in acoustic impedance generated at the interface between tissues and rigid SiO 2 surfaces. 17,[29][30][31][32] SiO 2 NPs also assure prolonged stability with respect to nanobubbles because bubble lifetime is limited by gas diffusion kinetics, whereas solid particles do not suffer from such limitations. Preliminary studies on the acoustic behaviors of SiO 2 NPs have demonstrated that SiO 2 NPs with a diameter of about 330 nm are very promising for use in CEUS at conventional diagnostic frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…SiO 2 NPs are common inorganic materials with natural echogenic properties, and they have recently been proposed as UCAs for CEUS due to the differences in acoustic impedance generated at the interface between tissues and rigid SiO 2 surfaces. 17,[29][30][31][32] SiO 2 NPs also assure prolonged stability with respect to nanobubbles because bubble lifetime is limited by gas diffusion kinetics, whereas solid particles do not suffer from such limitations. Preliminary studies on the acoustic behaviors of SiO 2 NPs have demonstrated that SiO 2 NPs with a diameter of about 330 nm are very promising for use in CEUS at conventional diagnostic frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Various nanomaterials, such as nano-bubbles and nano-droplets, have been used as ultrasonic contrast agents and have obvious advantages over traditional ultrasonic contrast agents. 32 Ultrasound is the most effective tool for the detection of structural neck diseases, and ultrasound-guided thyroid Fine-needle aspiration (FNA) is the gold standard for thyroid cancer diagnosis. 33,34 In clinical practice, there is a pressing need for a real-time, non-invasive, cost-effective, and precise diagnosis of thyroid cancer.…”
Section: Nanomaterials In Thyroid Cancer Diagnosismentioning
confidence: 99%
“…US is a mature clinical imaging technology for vascular diseases. Due to their limitations of insufficient penetration, low spatial resolution, and insensitivity, contrast agents such as microbubbles (MBs) or other acoustically active micro- or nanobubbles (NBs) are usually required ( Alphandéry, 2022 ). MBs or NBs are often filled with gases in the internal core; thus, they can create differences between the location sites and the surrounding tissues in echogenicity patterns, increasing ultrasound resolution and allowing visualization of targeted plaque composition.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%